Linguistic and Quranic Mind (The International Journal for Scientific Research, 2025)
This study addresses the problem of "linguistic reason" in the Arab-Islamic sphere from a philosophical and linguistic epistemological perspective, focusing on its intersection with the concepts of the Qur'anic reason, Arabic discourse, and the cultural framework in which it emerged. The study proceeds from the premise that language is not merely a tool for communication, but rather a cognitive system that establishes human representations of the universe and existence, reshaping these concepts throughout cultural and social history. This is demonstrated in the study of the history of reason in Arabic linguistic usage.The study analyzes the concept of "reason" in both linguistic and Qur'anic usages, highlighting the differences and intersections between them. It examines the history of the emergence of uses of reason in the Arab-Islamic sphere, highlighting the most important historical turning points in this formation, and drawing comparisons with Western philosophical conceptions of the concept of "logos." It also demonstrates how the Arab-Islamic reason was shaped through discursive and Qur'anic practice, where language became a network of conceptual and cultural relationships that connect knowledge, ethics, Sharia, and history. The results highlighted that the Arab linguistic mind was founded on an equation based on the inseparability of truth and value, and that the Qur'an contributed to reformulating rational concepts in Arab culture by establishing a cognitive and ethical dimension related to humanity and existence. The research also demonstrated that the linguistic mind is not merely a logical or abstract dimension, but rather a sociocultural practice shaped in light of the Arab and Islamic historical context.The research objectives were also consistent with the findings, as it sought to:1.     Clarify the nature of the linguistic mind and its role in shaping meanings and thought.2.     Analyze the interactive relationship between language and thought from a psycholinguistic perspective.3.     Review contemporary theories in understanding the mind's processing of language.
Keywords: Linguistic Mind; Qur'anic Mind; Arabic Discourse; Islamic Philosophy; Logos; Language and Knowledge